Territories of Abandonment. The Central Apennines and Uncultivated Countryside - Ottavia Aristone; Angela Cimini (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2020)
According to the data of CREA (Council for Agricultural Research and analysis of the Agrarian Economy) more than one third of the Italian territory is covered in woods, with an acceleration of 5.8% in the last decade. Of the 66,000 hectares that are generated on average per year, only a marginal quota is due to reforestation. Spontaneous reforestation has been seen mostly on plateaus and hills.